Heat transfer - Holman, J. P. (Jack Philip) (McGraw-Hill series in mechanical engineering, 2010)
One of the most popular heat transfer texts of its time, Holman's book is noted for its clarity, accessible approach, and inclusion of many examples and problem sets. This new edition features design-oriented problems, and improved pedagogy.